Lexical Paradigms of Yurii Izdryk’s Linguistic Picture of the World (Linguostylistic Studies, 2018)
The article considers the notion of Yurii Izdryk’s language picture of the world in the context of linguistic studies. The study sheds light on the mechanisms of creating the writer's linguistic picture of the world and argues that it is a complex, inexhaustible system of verbal reflections on reality. The author explores the literary works of Izdryk and draws a conclusion that realization and fixation of this system synthesize primarily the notions that dominate in the writer’s imagination, thus creating his individual artistic vocabulary. The author formulates a hypothesis that the specific features of Izdryk’s style in the novel Votsek, such as the lack of a linear plot, irrationality, “blurred” reality boundaries, the fragments of the memories, create the basis for using lexemes of peculiar semantics. The study has revealed the lexical paradigms, dominating in the Izdryk's linguistic picture of the world, with a focus on the lexical paradigm components of abstract notions, since they are uppermost in the person’s inner reflections and emotions. The writer’s linguosophy is an immersion into the inner world of the character verbalized via the paradigm of the names of abstract notions, among which lexemes with the negative sememes predominate. The author analyzes a linguistic paradigm of space that combines names of the realistic notions of space (such as earth, town, village, street, square, etc.) and the concept of the universe as a surreal substance, sense of the closed space. The article elucidates linguo-stylistic functions of the concepts that verbalize the subject of a human being as everyday culture and everyday traditions, including analysis of the lexical paradigms of male and femal. A numerous person's name paradigm has been divided into semantic groups with textual characteristics of each group. The name characteristic features with negative connotations are analyzed as dominating ones.
Keywords: language/linguistic picture of the world; literary text; lexical paradigm; writer’s linguosophy; linguo-stylistical function